Analisis Faktor-Faktor Yang Mempengaruhi Kunjungan Wisatawan Ke Kota Batu - Jeffry Daniel Haomoan Sihombing (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aimedto determine the effectofpeople income, travel costs, travel time, facilities, andcity brandingtovisitingBatu City. The researchmethodsusequantitativemethodwith adescriptive approach. This study usesprimary databy using aquestionnaireas a tool tocollectdata. Results of this study can be concluded that the reason tourists visit the Batu City are the travel time and facilities for tourism. People income variable and travel cost variable does not significantly affect to tourist visiting Batu City. While city branding influence significantly but have negative correlated to the tourists visiting Batu City. Keyword: tourism demand, city branding, travel cost